3 year outcomes of permanent pacemaker implantation after alcoholic septal ablation. (3rd October 2022) - Grazina, A; Ferreira, V; Cardoso, I; Garcia Bras, P; Viegas, J M; Aguiar Rosa, S; Fiarresga, A; Ramos, R; Castelo, A; Teixeira, A R; Teixeira, B; Jacinto, S; et al.
Abstract: Introduction: Patients with hypertrophic obstructive cardiomyopathy (HOCM) that remain symptomatic despite optimized medical therapy are often submitted to alcohol septal ablation (ASA). One of the most frequent complications is the complete hear block (CHB), requiring permanent pacemaker (PPM) in variable rates, up to 20% of the patients. The long-term impact of PPM implantation in these patients remains unclear. Objectives: This study aims to evaluate the long-term clinical outcomes in patients who implant PPM after ASA. Methods: In a tertiary center, patients who underwent ASA were consecutively enrolled prospectively. Patients with previous PPM or implantable cardio-defibrillator were from this analysis. The groups with and without PPM implantation after ASA were compared regarding baseline characteristics, procedure data and 3-year primary and secondary endpoints. Results: Between 2009 and 2020, 109 patients underwent ASA. 97 patients were included in this analysis (68% female, mean age 65.2 years-old). 16 patients (16.5%) required PPM implantation for CHB. In those, no vascular access, pacemaker pocket or pulmonary parenchyma complications were noted. The baseline characteristics regarding comorbidities, symptoms, echocardiographic and electrocardiographic findings were identical in the two groups, with statistically significant differences in the mean age (70.6y/o in the PPM group versus 64.1y/o) and in the beta-blocker therapy rates previously to the intervention (56% in the PPM group versus 84%). Procedure-related data showed higher creatine kinase (CK) peaks in the PPM group (1692U/L versus 1243U/L, p0.05), without significant differences in the alcohol dose (2.1ml in both groups, p0.33). At 3 years after ASA procedure, the primary endpoint (composite of all-cause mortality and all-cause re-hospitalization) showed a statistical tendency to a lower event rate in the group who implanted PPM (p-value 0.097, Graphic 1). The secondary endpoint (composite of all-cause mortality and cardiac cause re-hospitalization) did not show any significant statistical difference between the two groups (p-value 0.216, Graphic 2). Conclusions: The long-term endpoint analysis suggests that the outcomes in patients who implant PPM after ASA are non-inferior to those who do not, with a tendency to a lower rate of the endpoint composite of all-cause mortality and all cause re-hospitalizations. Funding Acknowledgement: Type of funding sources: None.